Stability and binding effects of silver(I) complexes at lipoxygenase-1. (August 2015) - Vrontaki, Eleni; Leonis, Georgios; Avramopoulos, Aggelos; Papadopoulos, Manthos G.; Simčič, Mihael; Grdadolnik, Simona Golič; Afantitis, Antreas; Melagraki, Georgia; Hadjikakou, Sotiris K.; Mavromoustakos, Thomas
Abstract An anti-inflammatory complex of Ag(I), namely [Ag(tpp)3(asp)](dmf) [tpp = triphenylphosphine, aspH = aspirin, dmf = N, N-dimethylformamide], was synthesized in an attempt to develop novel metallotherapeutic molecules. STD 1H NMR experiments were used to examine if this complex binds to LOX-1. The 1H NMR spectra in buffer Tris/D2O betrayed the existence of two complexes: the complex of aspirin and the complex of salicylic acid produced after deacetylation of aspirin. Nevertheless, the STD spectra showed that only the complex of salicylic acid is bound to the enzyme. Molecular docking and dynamics were used to complement our study. The complexes were stabilized inside a large LOX-1 cavity by establishing a network of hydrogen bonds and steric interactions. The complex formation with salicylic acid was more favorable. The in silico results provide a plausible explanation of the experimental results, which showed that only the complex with salicylic acid enters the binding cavity.